The power of Psalms in post-biblical Judaism liturgy, ritual and community - International Conference Psalms in Rituals from Antiquity to the Present 2018 Erfurt; Bergmann, Claudia D.; Rajak, Tessa 1946-; Kranemann, Benedikt 1959-; Ullrich, Rebecca (Leiden Boston Brill, 2023)
"The powerful poetry of the Hebrew Psalms articulates a unique range of experience, even in translation. They explore the deepest concerns of individuals and communities. They are central to the performance of religion for both Jews and Christians. New discoveries, such as the famous Dead Sea Scrolls, have transformed our view of their role in Judaism, as has modern re-evaluation of the complicated relationship between Judaism and Christianity. Here a group of leading scholars sheds fresh light on the uses of the Psalms in post-biblical Jewish life in a multi-cultural world"--
"The international conference "Psalms in Rituals from Antiquity to the Present," held on October 24-26, 2018, at the Max-Weber Kolleg in the University of Erfurt, Germany, aimed to showcase and also to build upon recent developments in what has become a very exciting field, bringing to it the distinctive perspective of the Research Centre "Dynamics of Jewish Ritual Practices in Pluralistic Contexts from Antiquity to the Present," which hosted the event. The Research Centre, which was funded from 2015 to 2020 by the Bundesministerium für Bildung und Forschung (BMBF), investigated the dynamic relationship of rituals in pluralistic contexts and specifically in Jewish and Christian religious traditions. While religious institutions often focus on tradition, invariability, and rootedness in history, the Research Centre has found and studied numerous examples of innovation and change in regard to religious ritual practices. This landmark conference approached the subject of the Psalms as a dynamic part of Jewish liturgy, ritual, and community formation from a broad perspective. ... This volume contains a selection of the papers delivered at that conference together with two additional papers, those of James Aitken and Laura S. Lieber, that were written specially for the volume"--Preface
English
Keywords: Bible -- Use -- Congresses; Bible -- Influence -- Congresses; Bibel; Bible; Since 586 B.C; Eschatology -- Biblical teaching; Psalmody -- History and criticism; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D -- Congresses; Jews -- History -- 70- -- Congresses; Einfluss; Frühjudentum; Judentum; Judaïsme - Histoire - 586 av. J.-C.-210 (Période postexilique) - Congrès; Juifs - Histoire - 70- - Congrès; Influence (Literary, artistic, etc.); Jews; Judaism - Post-exilic period (Judaism); Conference papers and proceedings; History; Konferenzschrift; Aufsatzsammlung